Impact of respectful maternity care and its outcome in a childbearing woman - K., Shwetha; Yadav, Anjalee; Jeetu, (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Respectful maternity care (RMC) is an individualised approach which emphasises on moral values and respect for human rights, and encourages behaviours that take into account women's preferences and the needs of both pregnant women and new mothers. The Indian Government has recently undertaken RMC under LaQshya to give respectable attention and care to the pregnant patients at medical facilities. Methods: It is a cross sectional study conducted in the department of obstetrics and gynaecology at a tertiary care hospital in Bhopal. Pregnant women who came for labour and delivery services were included in the study and all pregnant female–healthcare provider interactions during childbirth were taken for assessment. Results: Patient satisfaction survey of labour room done consecutively for 3 months revealed PSS score of 4.55, 4.51 and 4.51 in month 1, 2 and 3. Similarly, patient satisfaction survey of maternity operation theatre (OT) done consecutively for 3 months revealed PSS score of 4.59, 4.56 and 4.50 in month 1, 2 and 3. Conclusions: The study's results show that respectful maternity care is still in its budding stage despite the fact that women are noticing and reporting positive changes in maternity care practises. In order to improve maternal health outcomes for all women, there is a need for increased action, discussion, research, and advocacy on this crucial public health and human rights problem.